2023
DOI: 10.1002/jbm.b.35320
|View full text |Cite
|
Sign up to set email alerts
|

pH‐responsive resveratrol‐loaded ZIF‐8 nanoparticles modified with tannic acid for promoting colon cancer cell apoptosis

Xueqiang Sun,
Fuxin Li,
Lingyan Yuan
et al.

Abstract: Resveratrol (Res) is known for its potential in treating various types of cancers, with a particular advantage of causing minimal toxic side effects. However, its clinical application is constrained by challenges such as poor bioavailability, low water solubility, and chemical instability in neutral and alkaline environments. In light of these limitations, we have developed a pH‐responsive drug delivery nanoplatform, Res@ZIF‐8/TA NPs, which exhibits good biocompatibility and shows promise for in vitro cancer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In fact, in such conditions the slightly acidic tumor microenvironment generated by the Warburg effect could lead to a drop in the pH to around 5.5, with cancerous cells and tissues being more acidic than the healthy microenvironments. Thus, smart pH-sensitive nanocarriers have been engineered to target colon pathologies, especially through oral drug administration, in the context of IBD and colon cancer, enhancing the specificity and effectiveness of treatments [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. In particular, polyacid polymers, such as alginate and hyaluronic acid, are intrinsically suited for delivery in the gut; at an acidic pH, they can be found in their neutral shrunken form, protecting the drug during the passage through the stomach.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, in such conditions the slightly acidic tumor microenvironment generated by the Warburg effect could lead to a drop in the pH to around 5.5, with cancerous cells and tissues being more acidic than the healthy microenvironments. Thus, smart pH-sensitive nanocarriers have been engineered to target colon pathologies, especially through oral drug administration, in the context of IBD and colon cancer, enhancing the specificity and effectiveness of treatments [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. In particular, polyacid polymers, such as alginate and hyaluronic acid, are intrinsically suited for delivery in the gut; at an acidic pH, they can be found in their neutral shrunken form, protecting the drug during the passage through the stomach.…”
Section: Resultsmentioning
confidence: 99%
“…The Transwell and cell scratch assay results showed that RSV-loaded ZIF-8 inhibits cancer cell invasion and migration. The Hoescht 33342/PI and RT-qPCR results demonstrated that RSV-loaded ZIF-8 nanoparticles upregulate apoptotic gene expression in cancer cells ( Figure 14 and Figure 15 ) [ 200 ].…”
Section: Application Of Nanoparticles To Improve the Therapeutic Pote...mentioning
confidence: 99%
“…One of the key advantage of targeted delivery systems in precision medicine for colorectal cancer is the potential to overcome drug resistance. By delivering therapeutic agents directly to cancer cells, these systems can bypass resistance mechanisms that may be present in normal cellular pathways. , Additionally, targeted delivery reduces exposure to healthy tissues, minimizing side effects and improving the overall safety profile of the treatment. Moreover, targeted delivery systems contribute to the personalization of colorectal cancer treatment by tailoring therapeutic interventions to the unique molecular profile of each patient’s tumor.…”
Section: Future Directions and Emerging Technologiesmentioning
confidence: 99%